(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The work aims to find out a better way to perform colon cancer identification with the help of Resnet-18 algorithm in comparison with a Squeezenet algorithm to maximize the accuracy in finding rather than the existing method of prediction. Materials and Methods: A collection of 30 samples were picked for consideration; group 1 visualizing Resnet-18 classifier algorithm and finally group 2 is responsible for the Squeezenet algorithm. Thus G power calculation is done with a power of 80.5 and the alpha value is equivalent to 0.061. Results: When compared to the Squeezenet algorithm, the Resnet-18 classifier algorithm has attained an accuracy of 86.5060 % and 0.32754 which is somewhat greater than the existing method. ( Squeezenet algorithm attained an accuracy of 83.5433% and 0.28975) respectively. Conclusion: From the above statement it is evident that the Resnet-18 algorithm would be a better choice for predicting colon cancer and it is more effective.